SELECTION AND EVALUATION ABOUT HEALTHY OR MATURE PERSON CATEGORY FROM “BIG-FIVE” MODEL - García Hernández, Fernando Rubén (Anales de Psicología / Annals of Psychology)
It's investigated Psychology students' beliefs with regard to "mature person". It's suppossed that these sociocultural beliefs determine the rol and response of the future proffesional. This study is based on Implicit Theory of Personality, made use of "Big Five" of Tupes & Christal (1958, 1961) as structural perspective. 194 ss. (university students of 1º and 5º courses of Psychology) chose and evaluated adjetives, according to these were consistents with their own beliefs with regard to "mature person". The inicial taxonomy was selected from De Raad's adjetives (1992, p.24). Results indicated stability and consistence of all individuals' choices and evaluations: factors "Emotional Stability" and "Extraversion" were the more choosen and best evaluated. Assumming that, it's discussed about quality of student psychology's formation.